MRI advances on structural and functional changes in limbic system with premenstrual syndrome - Shan-Shan Li; Gao-Xiong Duan; De-Mao Deng (Meta-Radiology)
Premenstrual Syndrome (PMS) is a unique emotional disorder in women, characterized by a series of cyclical physical, emotional, behavioral, and cognitive symptoms that occur during the luteal phase of the menstrual cycle, often accompanied by significant functional impairment. Premenstrual Dysphoric Disorder (PMDD) is a severe form of PMS and is classified as a subtype of depressive disorders in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Neuroimaging studies have revealed structural and functional abnormalities in the limbic system of PMS/PMDD patients, particularly in areas such as the amygdala, hypothalamus, and hippocampus, which are closely related to clinical symptoms. These abnormalities may represent one of the central nervous mechanisms underlying PMS/PMDD. This review focuses on the structural and functional changes in the limbic system of PMS/PMDD patients as revealed by MRI, and summarizes the relevant research progress.